Hemodynamics and pathology of an enlarging abdominal aortic aneurysm model in rabbits. - Hongmei Chen; Yonghua Bi; Siyeong Ju; Linxia Gu; Xiaoyan Zhu; Xinwei Han (PLoS ONE, 2018)
Hemodynamics may play an essential role in the initiation and progression of abdominal aortic aneurysm (AAA). We aimed to study the mechanism of self-healing process by the changes of hemodynamics and pathology in an enlarging AAA in rabbits. Seventy-two rabbits were randomly divided into three groups. Rabbits underwent extrinsic coarctation and received a 10-minute elastase incubation in Group A and Group B. Absorbable suture used in Group A was terminated by balloon dilation at week 4. Diameter was measured after 1, 3, 5, and 15 weeks, computational fluid dynamics analysis was performed at week 3 and week 15. Rabbits were sacrificed after 1, 5, and 15 weeks for pathological and quantitative studies. The higher velocity magnitude, intensified bulk flow and obvious vortex formation were observed in Group A at week 3 instead of week 15. Both low wall shear stress and high relative residence time increased in Group B, however, high oscillatory shear index had relatively less increase compared with Group A. Aortic diameter reached a plateau at 5 weeks in Group A, which was significantly lower than in week 15 in Group B. Intimal hyperplasia, intima-media thickness increased significantly in Group A at week 5, significantly higher than in week 15 in Group B. Marked destruction of elastin fibers and smooth muscle cells occurred at week 1, and increased significantly at week 15 in Group A. Aneurysm exhibited strong expression of matrix metalloproteinase 9 and mouse anti-rabbit macrophage 11 at week 1, and showed a tendency to decrease. Matrix metalloproteinase 2 expression decreased significantly in Group B at week 15 compared with week 5 and Group A. In conclusion, the self-healing of rabbit AAA may attributed to the regeneration of smooth muscle cells. The turbulence flow caused by coarctation is associated with continuous growth of rabbit AAA and prevents the self-healing phenomenon.